Performance analysis of pair-wise error probability for 1/3 and 1/4 subcarrier mapping ICI-SC scheme in STFBC MIMO-OFDM system / Norhayati Abdullah - Abdullah, Norhayati (2015)
In the latest development of Orthogonal Frequency Division Multiplexing (OFDM) communication system, the system performance can be distracted by the Frequency Offsets (FOs) which can demolish the orthogonality of the subcarriers, increases the Inter-Carrier Interference (ICI) and can intensely deteriorate the system performance. As a result, Intercarrier Interference Self-Cancellation (ICI-SC) has been applied in numerous OFDM systems as a simple and impressive approach to overcome ICI. The need of higher data rates and improved coverage with an efficient bandwidth has revealed the potential of the combination of multiple input multiple output (MIMO) and Orthogonal Frequency Division Multiplexing (OFDM) as a powerful technique which can provide high data rates over frequency selective fading channels. ICI and maximum frequency diversity can also be achieved by manipulating the Space Time Frequency Block Codes (STFBCs) that uses spatial, time and frequency diversities which is implemented in the MIMO-OFDM system. The uncompromising frequency selective fading caused due to the multipath channel between the transmitter and the receiver and also the amount of time delay at the receiver from a signal travelling from the transmitter along different paths. This excess delay can cause both ISI to the adjacent OFDM symbols and the Inter-Carrier Interference (ICI) within the same symbol. An equalization technique is appended at the receiver to overcome ICI and ISI. Evaluation of Pair-Wise Error Probability (PEP) performance using STFBC MIMO-OFDM ICI-SC technique with one third and quarter subcarrier mapping scheme to diminish ICI due to Frequency Offsets (FOs) is achieved. Adaptive algorithms is also implemented with the specific equalizer in order to further improve the system performance. Thus, the objective of this research is to minimize ICI and ISI effects through STFBC ICI-SC subcarrier mapping scheme and equalization techniques. The simulation results expressively show that the one third method subcarrier mapping technique with Decision Feedback Equalizer (DFE) and adaptive algorithm can provide the best system performance compared to the existing subcarrier mapping methods .The results shows that by using the one-third subcarrier mapping scheme with an adaptive algorithm Normalised Least Means Square (NLMS), an efficient bandwidth can be achieved, ICI and ISI effects can be reduced with 24% of improvement compared to one-third subcarrier mapping Recursive Least Square (RLS) DFE in the MIMO-OFDM system.